Karakterisasi Performa Genset Diesel 5 KW Menggunakan Syngas Serbuk Kayu dengan Variasi Pembebanan - Erwin; Slamet Wiyono; Wahyu (UIR PRESS, 2022)
With the decreasing of world oil reserves, energy savings programs have started across the entire world. Recently, Indonesia has now become one of the importing countries for crude oil. Biomass gasification sustainability, especially in Indonesia, is very guaranteed because of the abundant availability of biomass in Indonesia. The goals of this study are examine the 5 kW diesel generator performance against various load with diesel fuel and diesel fuel plus syngas (synthetic gas) from sawdust. This research was carried out at Renewable Energy Laboratorium of Engineering Faculty UNTIRTA. The author performed this research using 5,2 kW total load of halogen lamp. In this research the load used was only at 3.2 kW because of the